2004
DOI: 10.1073/pnas.0307832100
|View full text |Cite
|
Sign up to set email alerts
|

Production of fertile offspring from genetically infertile male mice

Abstract: A number of recessive autosomal genes cause male infertility. Male mice homozygous for the blind-sterile (bs͞bs) and quaking-sterile (qk͞qk) gene mutations are sterile, because they either do not produce any spermatozoa or produce only a few abnormal spermatozoa. Mice lacking the cyclic AMP responsive-element modulator gene are sterile due to failure of spermiogenesis. All these mice, however, are able to produce fertile offspring when their spermatozoa or round spermatids are injected into oocytes of normal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
37
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 48 publications
4
37
0
Order By: Relevance
“…However, the intracytoplasmic injection of qk v spermatozoa resulted in normal live offspring. These findings indicate that although the qk v mutation affects functions necessary for proper sperm differentiation and fertilization, it does not affect other epigenetic factors necessary for syngamy and normal embryonic development (3).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…However, the intracytoplasmic injection of qk v spermatozoa resulted in normal live offspring. These findings indicate that although the qk v mutation affects functions necessary for proper sperm differentiation and fertilization, it does not affect other epigenetic factors necessary for syngamy and normal embryonic development (3).…”
mentioning
confidence: 86%
“…Very few morphologically abnormal immotile spermatozoa are present in the semen of qk v males, because spermatids fail to complete differentiation. A recent report (3) showed that sperm from qk v semen and testes are unable to fertilize mouse oocytes in vitro. However, the intracytoplasmic injection of qk v spermatozoa resulted in normal live offspring.…”
mentioning
confidence: 99%
“…This is especially true for C57BL͞6 (B6) mice, most frequently used for generation of genetically engineered mice. This problem has been overcome by partial zona dissection before in vitro fertilization (3) or intracytoplasmic sperm injection of frozenthawed or freeze-dried spermatozoa (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Immature male germ cells such as spermatids and spermatocytes are currently used to produce offspring (8)(9)(10)(11) when spermatozoa cannot be obtained due to spermatogenic arrest because of genetic mutations or as the result of in vitro manipulation of germ cells (7,10,11). Therefore, cryopreservation of these immature sperm cells is necessary, but they suffer more cryodamage than mature epididymal spermatozoa.…”
mentioning
confidence: 99%
“…Some mutant, transgenic, and gene-targeted males are infertile because of defective spermiogenesis. The infertility of such males has been overcome by injection of spermatids into normal oocytes (6)(7)(8)(9). However, if the gonads of animals of interest lack germ cells, cloning would be the only way to propagate such lines.…”
mentioning
confidence: 99%